Radiographic evaluation of the quality of root canal treatment in a Bangladeshi population - Nazneen, Rafia; Karmaker, Rajesh; Begum, Gulnar; Amin, Nurul (IMC Journal of Medical Science, 2020)
Background and objective: Root canal treatment (RCT) has a high rate of success, when performed by properly trained dental surgeons. However, the failure rate is inappreciably high when the same procedure is done by less experienced dental graduates having no specialization on endodontics. This study was conducted to evaluate the technical quality of RCT performed by practicing dental graduates on Bangladeshi patient. Methods: This cross-sectional study was conducted in the Department of Dentistry of BIRDEM General Hospital Dhaka over a period of 6 months from January to June 2019. Radiographs of patients who had undergone RCT in last 6 months were included in the study. Parameters used to evaluate the obturation of the root canal were presence of root-filled, posts and voids. The RCT was assessed for filling at the end of the root with radiographic apex, the density of the filling material and taper from the orifice to apex. The quality of RCT was evaluated as totally unacceptable (score: 0-2), poorly acceptable (score: 3-4), acceptable (score: 5) and perfect (score: 6) based on the treatment score. Post-treatment complications were determined by furcation and cavity wall perforation, transportation, root perforation, instrument breakage, ledge formation, voids and missed canal. Result: A total of 180 postoperative readable radiographs with post root-canal treatment were evaluated. Evaluation of the technical quality of RCT revealed that 56% of the RCTs were of standard quality (41.7% were of perfect quality and 14.4% were of acceptable quality). The rest 23.3% were poorly acceptable and 20.6% were totally unacceptable. Majority (92.8%) of the obturation of the root canal revealed that roots were filled with sealing materials; however, 8.9% exhibited posts and 36.7% demonstrated voids. A sizable portion of the root canal obturation was unacceptable in terms of its length (12.2%), density (20%) and tapering (16.7%). Total 132 (73.3%) teeth developed at least one complication. Under filling and voids were predominant complications (42.8% and 41.1% respectively) followed by root perforation (12.2%), transportation (11.7%), ledge formation (5%), instrument breakage (2.8%) and missed canal (3.3%). Conclusion: The study concluded that over forty percent of the RCTs performed by dental graduates having no specialization on endodontics are of substandard quality and hence not acceptable. Ibrahim Med. Coll. J. 2019; 13(2): 59-64